(untitled) (Journal Of Educational and Psychological Researches, 2010)
The compensatory health beliefs and their relation to the health self-regulation The idea of health promotion is set from the philosophy that good health is the outcome of the accumulative personal achievement. It includes, on the individual run, developing the health habits at an early stage, and maintaining them in the two stages of adulthood and old age. For the psychologist , the idea of developing health includes the development of an intervention system aiming at helping people perform healthy practices and change those practices that damage health. Literature indicate that the individual when performing an unhealthy practice, this refers to a certain health problem for him which would lead to a change in his behavior and activities a compensatory for the unhealthy behavior. That is what we called the compensatory health beliefs which help to promote the person’s healthy habits. For example, the persons knows that smoking damages his health, yet he smokes and performs a compensatory behavior that lighten that damaging behavior. For health self-regulation, it explains who people are involved in some of the healthy behaviors and are subject to treatment like advancing some other healthy behaviors, and pays attention to the individualistic motivation of the healthy behavior as the personal motivation expressed according to certain behaviors. Several objectives were put like: 1) devising a scale for the compensatory health beliefs for state employees. 2) measure the compensatory health beliefs for state employees. 3) knowing the differences in health beliefs according to the variables : (i) gender (ii) education. 4) devising a scale of health self-regulation for state employees. 5) knowing the differences in health self-regulation according to the variables : (i) gender (ii) education. 6) measuring the correlative relationship between the health beliefs and self-regulation . The two scale were prepared by researchers according to the employing of theoretical perspectives each in accordance to its theoretical origin. The scales were applied on a sample of 100 employee in 100 female and 100 male employee. The psychometric features of the two scales were derived and the following results were found: • The sample have compensatory health beliefs. • There are statistically significant differences in health beliefs according to the variable of gender for the females. • There were no statistically significant differences according to the variable for education. • The sample members do not have healthy self-regulation. • There were no statistically significant differences in health self-regulation according to the variable for gender. • There were differences self-regulation according to the variable for education. • There were no statistically significant differences according to the variable for education. The research came up to recommendations and suggestions that are suitable with the findings.